Transforming Mathematics Learning: Students' Integrative Skills in Technology and Pedagogy - Turmuzi, Muhammad; Hikmah, Nurul; Junaidi, Junaidi (Bright Publisher, 2025)
In the digital age, mastering the topic or developing pedagogical design skills alone is no longer sufficient for instructors or aspiring math educators. They also need to be able to make connections between the two. In addition, other specialized abilities are required, such as the ability to use technology for learning (technological skills). Technological Pedagogical and Content Knowledge (TPACK) is a common term for this skill. TPACK is a framework that helps educators integrate technology into learning effectively. TPACK covers three main types of knowledge-Technology, Pedagogy, and Content, and how the combination of these three elements creates a more meaningful learning experience for students. This study aims to assess the TPACK teaching abilities of aspiring mathematics teachers in the Microteaching course. This research uses a qualitative descriptive method, which describes the object of research in its original form without quantitative measurement or manipulation of variables but focuses on describing the observed phenomena. In this instance, the study provides a general picture of how well math education students comprehend and utilize their TPACK. A Likert scale measures an individual's or group's attitudes, views, and perceptions concerning social phenomena to ascertain their understanding of TPACK. Twenty University of Mataram students enrolled in the Microteaching course in Mathematics Education served as the research subjects. Based on the findings of the research and discussion, it can be said that students applying TPACK to learning have an average score of 3.88 medium categories for technological pedagogical knowledge, 3.82 medium categories for pedagogical knowledge, and 3.63 medium categories for content knowledge. Since most students are already familiar with the TPACK instrument, their total TPACK ability has an average score of 3.89, which is considered to be medium.